Bioenrichment of Papaya Leaf Meal With Different Feed Formulations on Growth Performance of Tilapia (Oreochromis niloticus) - Ricky Febrinaldy Simanjuntak; Ira Maya Abdiani; Perdiansyah Perdiansyah; Riska Purnama Sari (UIN Sunan Gunung Djati Bandung, 2022)
The production and demand of tilapia (O. niloticus) in some countries continue to increase but are not matched by good growth quality. Several methods have been used to increase growth, such as the use of synthetic hormones and radiation, however, the methods require such a high cost. Thus it needs to be investigated the potential replacement with natural prooduct. Papaya leaf contains papain enzyme thought to be able to improve the growth performance of fish body weight through the conversion of proteins into amino acids. The purpose of this study was to investigate the growth performance of tilapia (O. niloticus) fish that were given papaya meal (C. papaya) treatments. The concentrations pellet with papaya meal respectively T1(feed with 0 grams of papaya leaf meal), T2 (administration of papaya leaf meal with 1.25 g/kg feed), T3 (administration of papaya leaf meal with 1.75 g/kg feed), T4 (administration of papaya leaf meal with 2 g/kg feed), T5 (administration of papaya leaf meal with 2.25 g/kg feed). Parameters analyzed included: absolute length growth, absolute weight, specific growth rate, FCR survival rate and, water quality. The results showed that the highest weight growth of tilapia fed with the administration of papaya leaf meal was found at T4 of 21.23 grams. In the specific weight, the optimal treatment was found in T4 with a percentage of 20.97%. In the length growth of tilapia, it was known that the T1, T4 and T5 had highest lengths when compared to other treatments and the highest survival rate of tilapia (O. niloticus) was in the T2, T3, T5 treatments of 73%. The optimal FCR value was found in the T4 treatment of 1.14. Based on the results of the study, it can be concluded that the administration of papaya leaf flour can increase the growth performance of tilapia.Al-Nemrawi, N. K., Alsharif, S. S. M. & Dave, R. H. (2018). Preparation of Chitosan-TPP Nanoparticles: The Influence of Chitosan Polymeric Properties and Formulation Variables. International Journal of Applied Pharmaceutics, 10(5), 60–65. Awaludin., Simanjuntak, R. F. & Jumsan. (2020). Modifikasi Pakan Buatan untuk Meningkatkan Pertumbuhan dan Kelangsungan Hidup Udang Windu (Penaeus monodon). Majalah Ilmiah Biosfera, 37 (3). 168-174Amri, K. & Khairuman. (2003). Membuat Pakan Ikan Konsumsi. Agromedia Pustaka. Tangerang.Boyd, C. E. (1982). Water Quality Management for Pond Fish Culture. Amsterdam: Elsevier Scientific Publishing Company.De Silva, S. S. & Anderson, T. A. (1995). Fish Nutrition In Aquaculture. Aquaculture Series 1. London, Chapman and Hall. Dongoran, D. S. (2004). Pengaruh Activator Sistein dan Natrium Klorida Terhadap Aktivitas Papain. Jurnal Sains Kimia, 8 (1). 26-28Effendi, M. I. (2002). Biologi Perikanan. Cetakan Kedua. Yayasan Pustaka Nusantara, Yogyakarta:Effendi, M. I. (2003). Telaah Kualitas Air. Kanisius: Yogyakarta. 'Haetami, K., Junianto. & Andriani, Y. (2005). Tingkat Penggunaan Gulma Air Azolla pinnata dalam Ransum Terhadap Pertumbuhan dan Konversi Pakan Ikan Bawal Air Tawar. Laporan Penelitian. Universitas Padjadjaran, JatinangorHandajani, H. & W. Widodo. (2010). Nutrisi Ikan. Malang: UMM Press. Irawati, D., Rachmawati, D. & Pinandoyo. (2015). Performa Pertumbuhan Benih Ikan Nila Hitam (Oreochromis niloticus bleeker) Melalui Penambahan Enzim Papain dalam Pakan Buatan. Journal of Aquaculture Management Technology, 4 (1). 1-9.Isnawati, N., Sidik, R. & Mahasri, G. (2015). Potensi Serbuk Daun Pepaya untuk Meningkatkan Efisiensi Pemanfaatan Pakan, Rasio Efisiensi Protein Dan Laju Pertumbuhan Pada Budidaya Ikan Nila (Oreochromis niloticus). Jurnal Ilmiah Perikanan dan Kelautan, 7(2).Mareta, E. R., Subandiyono, & Hastuti, S. (2016). Pengaruh Enzim Papain dan Probiotik dalam Pakan Terhadap Tingkat Efisiensi Pemanfaatan Pakan dan Pertumbuhan Ikan Gurami (Osphronemus gouramy). Jurnal Sains Akuakultur Tropis, 1 (1):21-30.Murjani, A. (2011). Budidaya Beberapa Varietas Ikan Sepat Rawa (Trichogaster Trichopterus Pall) Dengan Pemberian Pakan Komersial. Jurnal Fish Scientiae, 1 (2): 214-133.Prakoso, T. (2014). Pengaruh Suhu yang Berbeda Terhadap Laju Pertumbuhan Benih Ikan Gurami (Osphronemus gouramy lac) didalam Akuarium. Skripsi. Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Antakusuma. Riyanti. A., Susanto. A. & Sukarti, K. (2014). Penambahan Tepung Buah Pepaya (Carica papaya). Dalam Pakan Terhadap Pertumbuhan dan Efesiensi Pakan Pada Ikan Nila Gift (Oreochromis sp) Ukuran 3-5 cm. Jurnal Ilmu Perikanan Tropis, 30 (1). 60-67Robinette, H. R. (1976). Effect of Sublethal of Ammonia on the Growth of Channel Catfish (Ictalarus punctatus R). Frog. Journal Fish Culture, 38 (1). 26-29Rukisah., Simanjuntak, R. F. & Anugrah, W. (2021). Pengaruh Pemberian Pakan Buatan dari Kombinasi Tepung Cacing Tanah (Lumbricus rubellus) dan Tepung Daun Pepaya Terhadap Pertumbuhan Ikan Nila. Jurnal Harpodon Borneo, 14 (1). 39-46Rukmana, H. R. (1997). Ikan Nila Budidaya dan Prospek Agribisnis. Yogyakarta: Kanisius.Sagita, F., Rachmawati, D. & Suminto. (2017). Pengaruh Penambahan Enzim Papain Pada Pakan Komersial Terhadap Efisiensi Pemanfaatan Pakan, Laju Pertumbuhan,Kelulushidupan Ikan Sidat (Anguilla bicolor). Journal of Aquaculture Management and Technology, 6(4). 77-84.Salsabila, M. & Suprapto, H. (2018). Teknik Pembesaran Ikan nila (Oreochromis niloticus) di Instalasi Budidaya Air Tawar Pandaan, Jawa Timus. Journal of Aquaculture and Fish Health, 7(3). 118-123Simanjuntak, R. F., Abdiani, I. M. & Verawati. (2018). Bioenrichment Tepung Pepaya (Carica Papaya) dengan Formulasi Pakan yang Berbeda pada Performa Pertumbuhan Ikan Nila (Oreochromis niloticus). Jurnal Harpodon Borneo, 11 (2). 59-68.Simanjuntak, R. F. & Ridwansyah. (2020). Membangung Keterampilan Mahasiswa Perbatasan Kaltara Melalui teknologi dan Manajemen Pembuatan Pakan Ikan Pada Masa Pancemi dan Pasca Covid-19. Jurnal Pengabdian Masyarakat Borneo, 4 (2). 143-150SNI 7550.2009. (2009). Produksi Ikan Nila (Oreochromis niloticus Bleeker) Kelas Pembesaran di Kolam Air Tenang. Badan Standardisasi nasional. JakartaSulasi, S., Hastuti, S. & Subandiyono, S. (2018). Pengaruh Enzim Papain dan Probiotik pada Pakan Buatan terhadap Pemanfaatan Protein Pakan dan Pertumbuhan Ikan Mas (Cyprinus Carpio). Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2 ()1, Zonneveld, N., Huisman E. A. & Boon, J. H. (1991). Prinsip-Prinsip Budidaya Ikan. Jakarta: Gramedia Pustaka Utama.